The Concept of Knowledge Management and Transport Exchanges in Supply Chain Management - Katarzyna HUK (Communications of International Proceedings, 2021)
The development of the economy is related to the development of knowledge and technology. The changes that we can observe from the industrial economy to the age of knowledge are influencing the growth of intangible assets. Currently, knowledge and intellectual capital are able to create the highest income for business. It is essential for any organization to acquire knowledge, share it and retain it in enterprises. In this study, the relationship between the concept of knowledge management and the presence of information brokers in supply chains, including transport exchanges, will be presented. The aim of the article is to present this dependence and to present the possibility of creating knowledge for the needs of transport companies on the selected stock exchange. An example will concern transport companies and their use in the Covid-19 pandemic.
Keywords: knowledge management; information brokers; transport exchanges; knowledge bases; transport companies in the time of the Covid-19 pandemic